2006
DOI: 10.1007/s10350-006-0694-z
|View full text |Cite
|
Sign up to set email alerts
|

Who are Susceptible to Pseudomembranous Colitis Among Patients with Presumed Antibiotic-Associated Diarrhea?

Abstract: Advanced age and long hospital stay may make patients with presumed antibiotic-associated diarrhea susceptible to pseudomembranous colitis. Therefore, pseudomembranous colitis should be first suspected in cases with presumed antibiotic-associated diarrhea having such risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Karlstrom et al [19] and Yeom et al [20] have reported that ages ≥60 years showed a high incidence of CDC. Lee et al [21] have reported that ages ≥70 years are an independent risk factor in multivariate analysis. They also explained that the increased incidence is related to a decrease in immunity through the aging process and an increase in the incidence of underlying disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karlstrom et al [19] and Yeom et al [20] have reported that ages ≥60 years showed a high incidence of CDC. Lee et al [21] have reported that ages ≥70 years are an independent risk factor in multivariate analysis. They also explained that the increased incidence is related to a decrease in immunity through the aging process and an increase in the incidence of underlying disease.…”
Section: Discussionmentioning
confidence: 99%
“…Long hospitalizations have been reported to be an independent risk factor for CDC in many studies [21-23]. Postoperative complications, such as ileus, deep surgical site infection, leakage or urinary tract infection, can prolong hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Dabei ist hervorzuheben, dass auch eine bis 2 Monate zurück-liegende Antibiotikagabe zu einer CDAD prädisponiert. Weitere Risikofaktoren sind Krankenhausaufenthalt und fortgeschrittenes Alter [20]. Das Risiko, an einer CDAD zu erkranken, ist im Alter >65 Jahren 20-mal höher als im Alter <20 Jahren [19].…”
Section: Pathogenese Und Klinikunclassified
“…To the best of our knowledge, no prospective study has examined the risk factors of PMC. However, Lee et al12 published a retrospective study assessing risk factors of PMC in 2006. The aim of this study was to identify the risk factors of PMC that can be easily applied to the treatment of patients with HAD.…”
Section: Introductionmentioning
confidence: 99%